The Cost of Living in Ancient Greece - Morales Harley, Roberto (2014)
The paper focuses on the most relevant economic aspects of Ancient Greece, more specifically, 5th century BC Athens. It explores the Greek notion of economy, the monetary system, the financial administration and the labor market, in order to contextualize the cost of living. The examples on this matter take into account the products’ costs and the people’s wages.